Loosening of tibia baseplates after total knee arthroplasty: Evaluation of pull-out strength of tibia baseplate-cement Interface. (December 2021) - Rebgetz, Paul; Kovacs, Alex; Bochat, Kieran; Hayes, Alex; Clark, Gavin; Blakeney, William; Pabbruwe, Moreica
Abstract: Background: Aseptic loosening is reported as the leading cause of revision total knee arthroplasty on the Australian National Joint Replacement Registry. Loosening of cemented tibial baseplates has been correlated with type of cement used, cementing technique, and cement contamination with biological material. The aim of this study was to evaluate the effect of cementing application and techniques including surface contamination and cement viscosity on fixation strength of tibia baseplates/cement interface. Methods: Mechanical assessment of the fixation strength of tibia baseplates/cement interface was tested using a pull-out test on a material testing system. Different tibial baseplate design, cementing techniques, cement viscosity and contamination of the implant/cement interface with bone marrow were assessed to determine if they influenced force required to disrupt the cement/implant interface (pull-out strength). Findings: The model with contamination of the cement prosthesis interface demonstrated a lower pull-out strength ( p < 0.001). The model with the keel and baseplate cemented showed a higher pull-out strength compared to cementing the baseplate alone (p < 0.001). The use of low-viscosity cement resulted in a significantly higher failure force ( p = 0.002) compared to high-viscosity cement when cementing the baseplate alone. Interpretations: Biomechanical testing demonstrated improved fixation with cementing the tibial keel and keeping surfaces free from contamination during the cementation process. Highlights: Biomechanical study assessing pull-out strength as a risk of aseptic loosening Bone marrow contamination of the cement significantly reduced pull-out strength Pull-out strength was increased with cement applied to the keel and baseplate